Penerapan Media Truth Or Dare untuk Meningkatkan Pemahaman Materi pada Pembelajaran PPKn Siswa Kelas V SD Inpres Jongaya Kecamatan Tamalate Kota Makassar - Safar Muhaymin; Muhajir Muhajir; Musdalifah Syahrir (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The main problem in this research is how to apply Truth or Dare card media to improve understanding of the material in PPKn learning for fifth grade students at SD Inpres Jongaya District. Tamalate City. Makassar. This research aims to determine the application of Truth or Dare card media to increase understanding in PPKn learning for fifth grade students at SD Inpres Jongaya District. Tamalate City. Makassar. This type of research is class action research (Class Action Research) which consists of two cycles where each cycle is carried out in two meetings. Research procedures include planning, implementing actions, observing, reflecting. The subjects in this research were fifth grade students at SD Inpres Jongaya District. Tamalate City. Makassar as many as 32 people. The results of the research show that in the first cycle there were 16 students who got a score ≥70 with a learning completion percentage of 50%. Meanwhile, in cycle II, there were 30 students who got a score of ≥70 with a learning completion percentage of 94%. Based on the research results above, it can be concluded that the application of Truth Or Dare media to fifth grade students at SD Inpres Jongaya, Tamalate District, Makassar City can improve understanding of the material in Civics learning.